Diagnosis of right bundle branch block: a concordance study - M. Alventosa-Zaidin; G. Pera; C. Roca Saumell; N. Mengual Miralles; M. V. Zamora Sanchez; T. Gros Garcia; L. Guix Font; M. Benitez Camps; J. Francisco-Pascual; J. Brugada Terradellas (BMC Family Practice, 2019)
Abstract Background Right bundle branch block is one of the most common electrocardiographic abnormalities. Most cases of right bundle branch block are detected in asymptomatic patients in primary care, so a correct interpretation of electrocardiograms (ECGs) at this level is necessary. The objective of this research is to determine the degree of concordance in the diagnosis of incomplete and complete right bundle branch block between four primary care researchers and a cardiologist. Methods The research design is a retrospective cohort study of patients over 18 years of ages of patients over 18 years of ages who underwent an ECG for any reason and were diagnosed with right bundle branch block by their physician. The physicians participating, 4 primary care researchers and a cardiologist were specialized in interpreting electrocardiographic records. The diagnosis of incomplete and complete right bundle branch block was recorded and other secondary variables were analysed. In case of diagnostic discordance between the researchers, the ECGs were reviewed by an expert cardiologist, who interpreted them, established the diagnosis and analysed the possible causes for the discrepancy. Results We studied 160 patients diagnosed with right bundle branch block by their general practise. The patients had a mean age of 64.8 years and 54% of them were men. The concordance in the diagnosis of incomplete right bundle branch block showed a Fleiss’ kappa index (k) of 0.71 among the five researchers and of 0.85 among only the primary care researchers. The k for complete right bundle branch block was 0.93 among the five researchers and 0.96 among only the primary care researchers. Conclusion The interobserver agreement in the diagnosis of right bundle branch block performed by physicians specialized in ECG interpretation (primary care physicians and a cardiologist) was very good. The variability was greater for the diagnosis of incomplete right bundle branch block.